Mobile Colistin Resistance (mcr) Gene-Containing Organisms in Poultry Sector in Low- and Middle-Income Countries: Epidemiology, Characteristics, and One Health Control Strategies - Madubuike Umunna Anyanwu; Ishmael Festus Jaja; Charles Odilichukwu R. Okpala; Emmanuel Okechukwu Njoga; Nnenna Audrey Okafor; James Wabwire Oguttu (MDPI AG, 2023)
Mobile colistin resistance (mcr) genes (mcr-1 to mcr-10) are plasmid-encoded genes that threaten the clinical utility of colistin (COL), one of the highest-priority critically important antibiotics (HP-CIAs) used to treat infections caused by multidrug-resistant and extensively drug-resistant bacteria in humans and animals. For more than six decades, COL has been used largely unregulated in the poultry sector in low- and middle-income countries (LMICs), and this has led to the development/spread of mcr gene-containing bacteria (MGCB). The prevalence rates of mcr-positive organisms from the poultry sector in LMICs between January 1970 and May 2023 range between 0.51% and 58.8%. Through horizontal gene transfer, conjugative plasmids possessing insertion sequences (ISs) (especially ISApl1), transposons (predominantly Tn6330), and integrons have enhanced the spread of mcr-1, mcr-2, mcr-3, mcr-4, mcr-5, mcr-7, mcr-8, mcr-9, and mcr-10 in the poultry sector in LMICs. These genes are harboured by Escherichia, Klebsiella, Proteus, Salmonella, Cronobacter, Citrobacter, Enterobacter, Shigella, Providencia, Aeromonas, Raoultella, Pseudomonas, and Acinetobacter species, belonging to diverse clones. The mcr-1, mcr-3, and mcr-10 genes have also been integrated into the chromosomes of these bacteria and are mobilizable by ISs and integrative conjugative elements. These bacteria often coexpress mcr with virulence genes and other genes conferring resistance to HP-CIAs, such as extended-spectrum cephalosporins, carbapenems, fosfomycin, fluoroquinolone, and tigecycline. The transmission routes and dynamics of MGCB from the poultry sector in LMICs within the One Health triad include contact with poultry birds, feed/drinking water, manure, poultry farmers and their farm workwear, farming equipment, the consumption and sale of contaminated poultry meat/egg and associated products, etc. The use of pre/probiotics and other non-antimicrobial alternatives in the raising of birds, the judicious use of non-critically important antibiotics for therapy, the banning of nontherapeutic COL use, improved vaccination, biosecurity, hand hygiene and sanitization, the development of rapid diagnostic test kits, and the intensified surveillance of mcr genes, among others, could effectively control the spread of MGCB from the poultry sector in LMICs.